Investigation of Trace Metals in Poultry Egg Purchased from Karachi, Pakistan - Raza, Rashid (Journal of Research (Science), 2025)
Heavy metals contamination in food commodities is a serious threat because of their toxicity, bio-magnification and bioaccumulation in food chain, which has been increasing day by day. Poultry egg is the major source of nutrients and protein. The current study was carried out to investigate alarming levels of heavy metals Cd, Co, Cu, Fe, Pb, and Mn in poultry egg sold in entire five districts of Karachi, Pakistan. The egg yolk and albumin were digested in nitric acid separately and heavy metal concentration was determined by atomic absorption spectrophotometer (AAS). The concentration of Cd, Co, Cu, Fe, Pb, and Mn in albumen of egg was found in a range of 0.10-0.16ppm, 1.36-2.60ppm, 2.92-5.55, 48.5-58.9ppm, 4.00-8.55 and 2.28-5.82ppm respectively. The concentration of Cd, Co, Cu, Fe, Pb, and Mn in yolk of egg was found in a range of 0.06-0.09ppm, 0.65-1.56ppm, 7.12-10.20ppm, 98.8-118.8ppm, 2.30-4.85ppm and 14.8-34.8ppm respectively. Heavy metals concentrations were found in descending order Fe> Mn> Cu> Pb> Co> Cd in egg albumin as well as egg yolk of sample analyzed for entire five districts of Karachi. The high levels of heavy metals in poultry eggs detected in the period of studies could be a serious risk to human health in the largest populated city of Pakistan, where limited resources are available for the prevention and controlling their levels in the food supply.